Embodied Time: Applied and Incidental Architectural Narratives - Owen Davıes; Laura Hanks (DEPARCH Journal of Design Planning and Aesthetics Research)
In this analysis of storytelling through building, encompassing a search for practical applications for how future buildings can embrace the passing of time, narrativity has been categorised into: the ‘applied’ or ‘artificial’, meaning the construction of a directed story, identity or philosophy; and the ‘incidental’ or ‘organic’, the accidental erosion and patination caused by weathering and human use. In ‘Building Time’, David Leatherbarrow considers three groupings for his analysis of buildings inhabiting the temporal dimension. The ‘Time of the Project’, the alterations, adaptations and adjustments made to a building, can be considered a prototype for ‘applied’ narrativity, while his ‘Time of the World’ can be linked to the gathering of ‘incidental’ narrativity. Leatherbarrow’s third aspect, the ‘Time of the Body’, can be compared to the phenomenological aspects linking these categories together, directing human passage and activity through design cues and through the traces of those who have come before (Leatherbarrow, 2021). At times these categories overlap and intertwine with each other, mirroring the idea that in the communication of narrative the “the corporeal is not more fundamental than the intellectual, but… are entangled” (Austin, 2012: 108). In summary, the aim is for an architecture that may “articulate the experiences of our very existence” (Pallasmaa, 2009 :19). Therefore, as time passes and our experiences become history, we can still tell our stories through the medium of building. This methodology to create buildings with a high degree of ‘story-ness’ was later tested in the design of a new library and literary museum. Based in Nottingham’s Lace Market, the existing tale of County House, a derelict and crudely adapted Georgian townhouse, was clarified, curated and secured, while the adjacent plots provided opportunities to experiment with applied and incidental narratives told through new buildings.